Plant-Derived Compounds in Hemp Seeds (Cannabis sativa L.): Extraction, Identification and Bioactivity—A Review - Virginia Tanase Apetroaei; Daniela Ionela Istrati; Camelia Vizireanu (Molecules)
The growing demand for plant-based protein and natural food ingredients has further fueled interest in exploring hemp seeds (Cannabis sativa L.) as a sustainable source of and nutrition. In addition to the content of proteins and healthy fats (linoleic acid and alpha-linolenic acid), hemp seeds are rich in phytochemical compounds, especially terpenoids, polyphenols, and phytosterols, which contribute to their bioactive properties. Scientific studies have shown that these compounds possess significant antioxidant, antimicrobial, and anti-inflammatory effects, making hemp seeds a promising ingredient for promoting health. Since THC (tetrahydrocannabinol) and CBD (cannabidiol) are found only in traces, hemp seeds can be used in food applications because the psychoactive effects associated with cannabis are avoided. Therefore, the present article reviews the scientific literature on traditional and modern extraction methods for obtaining active substances that meet food safety standards, enabling the transformation of conventional foods into functional foods that provide additional health benefits and promote a balanced and sustainable diet. Also, the identification methods of biologically active compounds extracted from hemp seeds and their bioactivity were evaluated. Mechanical pressing extraction, steam distillation, solvent-based methods (Soxhlet, maceration), and advanced techniques such as microwave-assisted and supercritical fluid extraction were evaluated. Identification methods such as high-performance liquid chromatography (HPLC) and mass spectrometry (MS) allowed for detailed chemical profiling of cannabinoids, terpenes, and phenolic substances. Optimizing extraction parameters, including solvent type, temperature, and time, is crucial for maximizing yield and purity, offering the potential for developing value-added foods with health benefits.